Strategies for Tackling Rural Banditry and Security Challenges for Sustainable Democracy in Nigeria - Aliyu Danmaigoro; Danbauchi I.S; Audu S; Dorh L.E (International Journal of Integrative Research, 2023)
In the northern states, rural banditry as a result of the farmer-herder conflict has become a threat, so rampant that the state apparatus has begun to intervene. The safety of life and property has received priority attention from the governments of various countries in the world, both democratic and military governments. It is generally believed that development cannot progress in an atmosphere of excessive conflict, violence, anxiety, fear and destruction of property. There is no denying the fact that the absence of security or insecurity can have a negative impact on the overall well-being of rural farmers. The purpose of this study is to investigate the challenges faced by rural farmers towards sustainable democracy and the role of rural farmers in overcoming rural bandits due to the spread of conflicts that have affected national security and sustainable democracy. These measures include military action, vigilante groups, security intelligence, and a suspension of illegal mining activities in the northern state. The recommendations include: Governments should enhance rural security through the use of digital technologies such as sophisticated surveillance and detection tools and neglected security management initiatives in rural areas should be developed and enriched to reduce democratic illiteracy in rural areas.